Modelling and efficiency assessment of vertically reinforced slab foundation of multi-storey building - Kanat T. Alenov; Yerik T. Bessimbayev; Kylyshbay A. Bissenov; Assylbek S. Shadkam; Sayat E. Niyetbay; Zhangazy N. Moldamuratov (Нанотехнологии в строительстве)
Introduction. The aim of this study is to investigate the structural behavior and effectiveness of slab foundations reinforced with vertical elements, a technique increasingly employed in civil engineering to improve the performance of foundations on weak, compressible soil. Traditional slab foundations often suffer from excessive settlement and low bearing capacity, especially under high loads from multi-storey buildings. Reinforcement of the soil base provides a viable solution to these challenges by improving stiffness and reducing deformation. Methods and Materials. The study is based on numerical modeling using the finite element method (FEM) in PLAXIS 3D software, applying the Hardening Soil model in accordance with Eurocode 7. A 9-storey building with a monolithic slab foundation was modeled, and different configurations of vertical reinforcing elements were analyzed. The key parameters varied in the simulations included the spacing (2×2 m, 3×3 m, and 5×5 m) and length (2.5 m, 5.5 m, and 9.5 m) of rein forcing elements. Soil properties were derived from site-specific geotechnical investigations. Results and Discussion. The analysis showed that reinforcing the slab foundation significantly reduced deformation (by a factor of three) and bending moments (by up to 60%) compared to the unreinforced case. The most efficient configuration was found to be concrete elements of 9.5 m length with 2×2 m spacing. The use of vertical reinforcement not only increased the bearing capacity of the foundation but also optimized the stress distribution within the soil mass, minimizing differential settlement. Conclusion. Vertically reinforced slab foundations provide a reliable and cost-effective solution for construction on weak soils. The study confirms that optimal design of reinforcing elements – particularly their length and spacing – plays a crucial role in improving foundation performance. These findings can be directly applied to enhance the design and safety of multi-storey building foundations under challenging geotechnical conditions.